Econometric analysis of consumers’ preference heterogeneity for yoghurt and ice cream products in Tanzania: A latent class model and mixed logit model - Michael L. Kadigi; Damas Philip; Gilead I. Mlay; Ntengua S. Mdoe (Heliyon)
In Tanzania, a growing upper and middle classes, particularly among urbanites, exhibit distinct preferences for higher-quality processed foods, including dairy products. This study examines variations in consumer preferences and their willingness to pay for yogurt and ice cream, which serve as stand-ins for processed milk products. The analysis is based on a discrete choice experiment involving 400 participants in Dar es Salaam. A random parameter logit model was utilized to account for preference heterogeneity, while latent class models (LCMs) were applied to uncover the underlying factors driving these differences in preferences. Our findings reveal three distinct consumer classes: processed milk sceptics (who prefer unprocessed dairy products), processed milk advocates (who prefer processed products), and neutral consumers (indifferent between processed and unprocessed milk). Preferences are influenced by product attributes, socioeconomic characteristics, and attitudes towards processed foods. The results indicate that Tanzanian consumers place the greatest value on sensory attributes, packaging, and the product's origin (local versus imported). This research offers fresh perspectives on the intricate preferences of dairy consumers in Tanzania, a topic that has been relatively underexplored. The findings suggest that producers and marketers must adapt to the dynamic market by balancing intrinsic and extrinsic factors against price. Understanding consumers' socioeconomic and product attributes is essential for increasing market share and effectively segmenting markets. These findings would be useful incorporated into strategic planning to enhance the competitiveness and sustainability of Tanzania's dairy industry.